Religion, theology and science - the correctness of the relationship and the relevance of complementarity - Oksana Gorkusha (Українське Pелігієзнавство, 2013)
The topic of synthesis or cooperation of science and religion is current in the contemporary intellectual-ideological context. Contrary to popular tendencies to substantiate the necessity and to offer an acceptable model of such synthesis, we will set the goal of determining the degree of correctness and expediency of such attempts.